Exotic snakes in São Paulo City, southeastern Brazil: Why xenophobia ? - Eterovic, A.; Duarte, M. R. (Kluwer Academic Publ, 2002)
Introduced exotic species cause environmental changes and threat public health in target sites. Illegal trade has enhanced this problem. To first report these risks in Brazil, exotic snakes found in São Paulo City (SPC) (23degrees32' S, 46degrees38' W), southeastern Brazil, and sent to Instituto Butantan between 1995 and 2000, were listed and characterized by their biological attributes. Seventy-six individuals of sixteen alien species were collected. Euriecians snakes, mainly booids, were predominant. Using multivariate techniques, their ecological niches were compared to those of 26 native species, as a way to point out the resource's availability. To evaluate the potential of successful implantation, two species absent in SPC and considered as problem snakes are included in these analyses: the brown treesnake Boiga irregularis and the habu Trimeresurus flavoviridis. There were niche similarities between these pest snakes, exotic booids and native viperids largely due to the similarities in the chosen prey (mammals), diel activity (nocturnal), color pattern (variegated) and body size (medium to large). To avoid predictable undesirable effects of implanted pest snakes, traffic control and punishment should be improved, as well as parallel environmental education programs.
Keywords: animal trade; biological conservation; Brazil; ecological niche; exotic species; snakes